MORTALIDADE DE OVOS DA TRAÃ‡A DA FARINHA ð˜ˆð˜¯ð˜¢ð˜¨ð˜¢ð˜´ð˜µð˜¢ ð˜¬ð˜¶ð˜¦ð˜©ð˜¯ð˜ªð˜¦ð˜ð˜ð˜¢ (ZELLET, 1879) (LEPIDOPTERA, PYRALIDAE) ATRAVÃ‰S DAS RADIAÃ‡Ã•ES GAMA DO COBALTO-60 - Estevam, Roseli do Carmo; Arthur, Valter; Wiendl, Toni Andreas; Wiendl, Frederico M. (REVISTA DE AGRICULTURA, 2020)
MORTALIDADE DE OVOS DA TRAÃ‡A DA FARINHA ð˜ˆð˜¯ð˜¢ð˜¨ð˜¢ð˜´ð˜µð˜¢ ð˜¬ð˜¶ð˜¦ð˜©ð˜¯ð˜ªð˜¦ð˜ð˜ð˜¢ (ZELLET, 1879) (LEPIDOPTERA, PYRALIDAE) ATRAVÃ‰S DAS RADIAÃ‡Ã•ES GAMA DO COBALTO-60